The diachronic typology of non-canonical subjects - Seržant, Ilja A.; Kulikov, L. I. (Studies in language companion series ;, 2013)
In this paper I have examined several instances in which an oblique constituent acquires canonical subject marking, i.e. nominative case and verbal agreement (in an accusative language). These instances show that an oblique constituent may acquire subject coding properties without being beforehand endowed with subject behavioural properties, if two requirements are met: (i) this oblique constituent must exhibit a considerable functional overlap with the prototypical subject in the given language and, (ii) there must be either no canonically case-marked subject in the construction at all, or th.